Implementation the science communication using multiple representation approach for pre service teacher in environmental physics course - M Yakob; D Mustika; H Saputra; S Sofyan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Multiple representation on Physics for Environment subject was implemented to improve the student scientific communication. Multiple representation is one of approaches in active-learning lecture which is oriented on the student. The students was given a chance to understanding the topic in their own way, included the idea and describing visual observation in scientific manuscript and oral presentation. The subjectswere pre service physics teacher in Environmental Physics course. Our data showed that multiple representation has been relatively well implemented, it was observed 58% at C level. This percent was achieved by indicators of science communication skill, such as scientific bright ideas, describing scientific observation in manuscript, explaining scientific phenomena, and interpreting the data in graph, image, equation or table. The percent indicated positive response on multiple representation approach.